FORMATION OF A HEALTHY LIFESTYLE OF A STUDENT THROUGH PHYSICAL CULTURE AND SPORTS - Gapparov Khafiz Zakhidovich; Akhmedov Hikmatilla Rakhmanberdievich (Scholar Express Journal, 2022)
The article deals with the main problems of a healthy lifestyle of a student, the role of physical culture and sports. The article also provides statistical data on the state of health of the younger generation.
Keywords: Physical Training; Sport; Health